Assessing the Effects of NCC and NSS Programs on the Development of Leadership Style, Accountability, and Social Maturity in Students - Yadav, Dr Shailesh Kumar; Yadav PhD, Pradeep Kumar (International Journal of Religion Education and Law, 2025)
This study examines the impact of National Cadet Corps (NCC) and National Service Scheme (NSS) programs on the development of leadership style, accountability, and social maturity among students. By employing a mixed-methods approach, the research analyzes quantitative data from surveys and qualitative insights from interviews conducted with participants involved in these programs. Findings indicate that involvement in NCC and NSS significantly enhances leadership skills, fosters a sense of accountability, and promotes social maturity. Students participating in these initiatives demonstrate improved decision-making abilities, enhanced teamwork, and a greater sense of civic responsibility. The study highlights the importance of these programs in shaping well-rounded individuals capable of contributing positively to society. Recommendations for program enhancements and further research directions are also discussed, emphasizing the need for integrating leadership training within existing frameworks. The National Service Scheme (NSS) is an Indian government-sponsored public service program conducted by the Department of Youth Affairs and Sports of the Government of India. NSS aimed at developing student’s personality through community service. This research project is projected to assess the effect of NSS camp on improvement in communication skill and leadership qualities in undergraduate students of Ayurveda. The empirical results of the study showed that the NSS training enabled students acquire specialized competence in communication skill.